2022
DOI: 10.1002/gps.5820
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of post‐stroke depression between social support and quality of life among stroke survivors: A meta‐analytic structural equation modeling

Abstract: Objectives:The aim was to confirm the relationship between social support (SS), post-stroke depression (PSD), and quality of life (QOL) and determine the mediating effect of PSD in stroke survivors. Additionally, we tested the impact of economic development level (in developed or developing countries) on the relationship between SS, PSD, and QOL.Methods: This study utilized meta-analytic structural equation modeling on systematically searched articles from PubMed, MEDLINE, Cochrane Library, Scopus, PsycINFO, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…Our results showed a significant negative correlation between the level of social support and depression scores, consistent with previous studies. 35,36 Lack of support from others can lead to a lack of spiritual comfort, inadequate financial support, and the capacity for basic health needs. 37 Likewise, they become more passive in social contact due to decreased general well-being, which contributes to the development of PSD.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed a significant negative correlation between the level of social support and depression scores, consistent with previous studies. 35,36 Lack of support from others can lead to a lack of spiritual comfort, inadequate financial support, and the capacity for basic health needs. 37 Likewise, they become more passive in social contact due to decreased general well-being, which contributes to the development of PSD.…”
Section: Discussionmentioning
confidence: 99%
“…This study has found that “help from others” and “opportunities for community activities” are the most important predictors of quality of life. Previous studies have shown that social support and community involvement are interrelated, and either is strongly associated with quality of life and also depression 36 . Depression in a stroke survivor is likely to be reflected in a low role‐emotion (RE) score, which is characteristic of type I individuals with a poor quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Depression in a stroke survivor is likely to be reflected in a low role‐emotion (RE) score, which is characteristic of type I individuals with a poor quality of life. Previous studies have shown that social support is a significant predictor of quality of life, mediated by poststroke depression 36 . Among aphasic stroke survivors, depression is known to be strongly correlated with decreased community participation and impaired quality of life 37 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations